Barsine amaculata, a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2016)
Barsine Walker, 1854 is a large genus of lichen-moths (family Erebidae, subfamily Arctiinae, tribe Lithosiini) including about a hundred of described species and widely distributed in Oriental tropics. A number of species is also known from the Russian Far East, Japan, Korea, China and Taiwan. The genus long time was treated as a synonym or a subgenus of Miltochrista Hübner, [1819] (Hampson 1900; Strand 1917; Reich 1937; Daniel 1951; 1952; 1955; Inoue 1980; Holloway 1982; Fang 1991; 2000; Černý 1995), and was revived by Holloway (2001). Many new species of the genus were described during last two decades (Fang 2000; Holloway 2001; Kaleka 2003; Černý & Pinratana 2009; Bucsek 2012; 2014; Dubatolov et al. 2012; Dubatolov & Bucsek 2013; Wu et al. 2013). The genus is under revision by authors of the present paper. During studies of Lithosiini materials collected in Vietnam, an undescribed Barsine species was found. The species is described below.